2021
DOI: 10.1002/dac.4994
|View full text |Cite
|
Sign up to set email alerts
|

A new hexagonal quadrature amplitude modulation aided media‐based modulation

Abstract: Summary In this paper, a new high‐data rated and energy‐efficient hexagonal quadrature amplitude modulation aided media‐based modulation scheme, called HQAM‐MBM, is proposed for the next‐generation communication systems. In MBM, mirror activation patterns (MAPs) of a reconfigurable antenna have been used to convey extra information in addition to conventional modulated symbols. Therefore, the MBM is seen as a promising index modulation (IM) scheme for the next generation of high‐data rated communication system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In the MBM technique, it is possible to achieve high SE with a fair amount of RF mirrors. The hexagonal quadrature amplitude modulation assisted media‐based modulation system, which is shortly called HQAM‐MBM, is proposed in Reference 15. In Reference 16, a novel system is proposed, combining MBM, SM, and dual‐polarized antennas in a MIMO system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the MBM technique, it is possible to achieve high SE with a fair amount of RF mirrors. The hexagonal quadrature amplitude modulation assisted media‐based modulation system, which is shortly called HQAM‐MBM, is proposed in Reference 15. In Reference 16, a novel system is proposed, combining MBM, SM, and dual‐polarized antennas in a MIMO system.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, AS techniques that increase the performance of wireless communication systems have drawn the attention of researchers. 25,26 In Reference 27, AS techniques are integrated into the STBC-SM system. It has been observed that the proposed system provides a better bit error rate (BER) performance than the traditional STBC-SM method.…”
Section: Introductionmentioning
confidence: 99%
“…Aydin is with the Department of Electrical and Electronics Engineering, Istanbul Medeniyet University, Istanbul 34857, Turkey (e-mail: erdogan.aydin@medeniyet.edu.tr) low-latency communication, coverage and mobility, as well as providing intelligent and dynamic systems that quickly adapt to changing environmental conditions and application types [3]. In this context, schemes such as media-based modulation [4]- [6], spatial modulation (SM) [7] and space shift keying (SSK) [8] use reconfigurable antenna to get rich scattering environments. SM and SSK techniques have been presented with other techniques due to index modulation's (IM) spectral and energy efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…A new hexagonal quadrature amplitude modulation aided media-based modulation scheme, called HQAM-MBM, is proposed in [3][4][5] . The proposed technique is high-data-rated and energy-efficient for next-generation communication systems.…”
mentioning
confidence: 99%
“…The current work concentrates on voice transmission, while image transmission is an intriguing area for future research that can be taken into consideration. Finally, other QAM modulation schemes, such as the ones proposed in [3][4][5] could be modified to incorporate UEP and compared with the schemes used in this work.…”
mentioning
confidence: 99%